2012
DOI: 10.1177/1049732312456604
|View full text |Cite
|
Sign up to set email alerts
|

A Psychological Perspective of Eye Floaters

Abstract: Patients experiencing flashes and spots in their perceptive fields often resort to consulting an ophthalmologist without finding an answer, mainly because these symptoms are not necessarily associated with pathology of the eye. The purpose of our research study was to understand the experience of these patients, differentiate among them, and propose different ways of treating them. We carried out an eye examination and echography, individual semistructured interviews, and dependency grids with 11 patients at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 53 publications
(57 reference statements)
0
26
1
Order By: Relevance
“…In a previous study one of us proposed that the different ways in which people experience illness depend on their ways of being and their tendency to confide in themselves or in others for help (Cipolletta, Beccarello, & Galan, 2012). The basic assumption of that study was that illness is linked to social and personal processes that govern the maintenance of our identity.…”
Section: A Constructivist Perspective On Health and Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study one of us proposed that the different ways in which people experience illness depend on their ways of being and their tendency to confide in themselves or in others for help (Cipolletta, Beccarello, & Galan, 2012). The basic assumption of that study was that illness is linked to social and personal processes that govern the maintenance of our identity.…”
Section: A Constructivist Perspective On Health and Illnessmentioning
confidence: 99%
“…This path is similar to Ginzburg et al's (2011) category of disconnection, that is, the tendency to have both low attentiveness and low sensitiveness. This is a precarious position because it may prevent people from recognizing and caring about some illness (see, Cipolletta et al, 2012).…”
Section: The Four Trajectories Of Experiences and Their Implications mentioning
confidence: 99%
“…The theoretical framework drawn on for this study is the constructivist perspective, which assumes that each person makes sense of events in a different way (Kelly, 1955); therefore, a disease can take on multiple meanings and a person's health status may change accordingly (Cipolletta & Amicucci, 2015;Cipolletta, Beccarello, & Galan, 2012;Cipolletta, Consolaro, & Horvath, 2014). For this reason, personal meanings and the distribution of dependencies were explored.…”
mentioning
confidence: 99%
“…Therefore, the question is how people distribute their dependencies when asking one person for something and another for something else. Previous research has shown that the distribution of dependency is implicated in how a person lives and copes with illness (Cipolletta & Amicucci, 2015;Cipolletta et al, 2012), and gives and receives care (Cipolletta, Marchesin, & Benini, 2015;Cipolletta, Shams, Tonello, & Pruneddu, 2013). More specifically, a higher distribution of dependencies enables patients to cope better with illness because they can reconstrue their personal role and accept help.…”
mentioning
confidence: 99%
“…This question may be considered in relation to patients' choice of confiding in themselves or in others for help. It deals with the distribution of dependency and it is involved in the way the person lives and copes with illness (Cipolletta et al, 2012(Cipolletta et al, , 2013aTalbot et al, 1991) and gives and receives care (Cipolletta et al, 2013b(Cipolletta et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%